Engagement Law (Supreme Court Decision Number 951 K/Pdt/2015) - Setiawan, Ferdiansyah Prawira Negara; Mantiri, Juttah Christian (CV. Rayyan Dwi Bharata, 2023)
An agreement or contract is a legal relationship between two or more people who promise to give rise to legal consequences by means of an agreement. Legal consequences in the form of mutual rights and obligations between the parties. As a rule, an agreement or contract begins with a conflict or disagreement of interests between the parties, and the formation of a contractual relationship usually begins with a process of negotiation between the parties. This research method uses descriptive analysis. It is a method of using collected data to describe or provide an overview of the research subject and to present generally accepted conclusions. Based on the case in the Supreme Court decision No. 951 K/Pdt/2015 if Defendant I issues a statement that the